BLIMP-1 Mediated Downregulation of TAK1 and p53 Molecules Is Crucial in the Pathogenesis of Kala-Azar - Saha, Gundappa; Chiranjivi, Adarsh Kumar; Khamar, Bakulesh M.; Prerna, Kumari; Kumar, Manish; Dubey, Vikash Kumar (Frontiers in Cellular and Infection Microbiology, 2020)
Precise regulation of inflammasome is critical during any pathogenic encounter. The whole innate immune system comprising of pattern recognition receptors (PRRs) relies on its ability to sense microbes. The fate of cellular death in infected cells depends mostly on the activation of these inflammasome, the dysregulation of which, due to functional manipulation by various pathogens, leads to be the cause of many human diseases. Here, an interesting finding has been observed which is related to how Leishmania donovani parasites exploit various host mediator molecules to cause immunosuppression. Here we report for the first time that the parasites check pyroptosis in the infected cells in-vitro by BLIMP-1 mediated suppression of TAK1 and p53 proteins. This might be one of the reasons how parasites evade the pro-inflammatory response of the host cells. Further understandings and validations are required to come up with better therapeutic approaches against kala-azar.